A study of diffusion tensor imaging in Duchenne muscular dystrophy. - FU Ya; WU Shi-wen (Chinese Journal of Contemporary Neurology & Neurosurgery, 2015)
Objective To observe the white matter and gray matter impairment of Duchenne muscular dstrophy (DMD) patients with diffusion tensor imaging (DTI). Methods Forteen male patients with DMD (6-11 years old) and 10 age - matched healthy boys participated into this study. All patients' diagnosis was based on typical signs and symptoms, serum creatine kinase (CK), electromyography, multiplex ligation-dependent probe amplification (MLPA) for DMD gene test and muscle biopsy results. All participants were scanned by DTI. The fractional anisotropy (FA) values of regions of interest (ROIs), including bilateral parietal lobe white matter, bilateral frontal lobe white matter, genu of corpus callosum, splenium of corpus callosum, bilateral caput nuclei caudati, bilateral anterior cingulate gyrus, bilateral cingulate gyrus, bilateral posterior cingulate gyrus, bilateral lenticular nucleus, bilateral anterior limb of internal capsule, bilateral posterior limb of internal capsule, bilateral thalamus, bilateral occipital lobe white matter, bilateral temporal lobe white matter, bilateral hippocampus, bilateral superior cerebellar peduncle and bilateral middle cerebellar peduncle, were measured. The data was analyzed and compared between control group and DMD group. Results Compared with control group, the FA value of splenium of corpus callosum in DMD group was significantly reduced (t = - 2.187, P = 0.045). No significant difference was found in FA values of other ROIs between 2 groups (P > 0.05, for all). Conclusions It is found in China for the first time that DMD patients had microstructural changes in splenium of corpus callosum. However, the correlation between this change and cognitive changes of DMD patients remains to be further studied.